Guidelines for developing a web application for the Southern Souvenir - Silpasert, Natthakamon; Buntamcharoen, Waritsanan; Mahapoj, Jirapong (Chalermkarnchana Academic Journal, 2024)
This study aimed to 1) study the development guideline for a web application for the Southern Souvenir Product Center, and 2) design and develop a web application for product management, inventory management, and online sales of the Southern Souvenir Product Center. The sample group used in this study was 250 customers of the Southern Souvenir Product Center through instruction. Research instruments: 1) Web application satisfaction assessment form. The research results found that the overall system was at the highest level ( = 4.50, S.D. = 0.56). When considering each aspect, 1) system efficiency and usefulness were at the highest level ( = 4.58, S.D. = 0.58); 2) system design was at a high level ( = 4.40, S.D. = 0.54); and 3) system support and services were at the highest level ( = 4.52, S.D. = 0.58), respectively.